2013
DOI: 10.1038/nature12569
|View full text |Cite|
|
Sign up to set email alerts
|

Slowly fading super-luminous supernovae that are not pair-instability explosions

Abstract: The high luminosity and slow decline of their light curves ( Fig PTF12dam is not detected in z P1 images on 1 January 2012, 132 days before the peak.Although their light curves match the declining phases of SN 2007bi and the PISN models quite well, PTF12dam and PS1-11ap rise to maximum light a factor of ~2 faster than these models.The spectra of PTF12dam and PS1-11ap show them to be similar supernovae. After 50 days from the respective light curve peaks, these spectra are almost identical to that of SN 2007bi … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
390
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(416 citation statements)
references
References 54 publications
22
390
4
Order By: Relevance
“…This is consistent with a 56 Ni-driven light curve, and suggestive of the explosion of a very massive star with a zero-age main sequence mass close to, or in excess of 100 M⊙. This scenario has been criticized (e.g., Nicholl et al 2013), but in our opinion the presence of forbidden emission lines of Fe in an amount compatible with the 56 Ni that is necessary to drive the light curve (Gal-Yam et al 2009) makes the Ni-driven scenario uncontroversial. The massive collapse scenario (Moriya et al 2010) agrees on this despite uncertainties.…”
Section: Introductionsupporting
confidence: 53%
“…This is consistent with a 56 Ni-driven light curve, and suggestive of the explosion of a very massive star with a zero-age main sequence mass close to, or in excess of 100 M⊙. This scenario has been criticized (e.g., Nicholl et al 2013), but in our opinion the presence of forbidden emission lines of Fe in an amount compatible with the 56 Ni that is necessary to drive the light curve (Gal-Yam et al 2009) makes the Ni-driven scenario uncontroversial. The massive collapse scenario (Moriya et al 2010) agrees on this despite uncertainties.…”
Section: Introductionsupporting
confidence: 53%
“…The peak luminosity, M g ≈ −21, is typical of these fast-declining events and fainter than those slowlyfading objects (for a larger sample comparison, we refer to Nicholl et al 2015a). The rise time and overall lightcurve width are very similar to SN 2011ke (Inserra et al 2013), SN 2006oz (Leloudas et al 2012, and SN 2010gx (Pastorello et al 2010) and much narrower than other events, such as PTF12dam (Nicholl et al 2013;Chen et al 2015) and LSQ14bdq (Nicholl et al 2015b). LSQ14mo appears to transition to a shallower de- 4000 4500 5000 5500 6000 6500…”
Section: Lightcurvementioning
confidence: 58%
“…In contrast, the PISN model can only explain slowly-fading lightcurve events, such as SN 2007bi, which was initially suggested to be a PISN (Gal-Yam et al 2009) based on a 56 Co decay-like tail. However, the relatively rapid rise time of similar SLSNe PTF12dam and PS1-11ap (Nicholl et al 2013;McCrum et al 2014) argues against this interpretation. Recently, Kozyreva et al (2016) demonstrated that radiative-transfer simulations have essential scatter depending on the input ingredients, a relatively fast rising time was found for the helium PISN model (Kasen et al 2011).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations